Long‐term evaluation (20 years) of the outcomes of subepithelial connective tissue graft plus coronally advanced flap in the treatment of maxillary single recession‐type defects. Issue 11 (10th August 2018) - Pini Prato, Giovan Paolo; Franceschi, Debora; Cortellini, Pierpaolo; Chambrone, Leandro
Abstract: Background: Subepithelial connective tissue graft with coronally advanced flap (SCTG + CAF) has been considered the best and most predictable root coverage procedure. Thus, the aims of this study are two‐fold: 1) to evaluate the long‐term outcomes following SCTG + CAF in the treatment of gingival recessions (GR) and 2) to explore the influence of several tooth/patient‐related factors on the stability of gingival margin at 1 year and at 5, 10, 15, and 20 years after surgery. Methods: Forty‐five patients with 45 maxillary GR (Miller's Class I or III) were treated with SCTG + CAF in a private practice between 1990 and 1997. Recession depth (RD), probing depth (PD), keratinized tissue (KT) width and patient/tooth‐associated variables were recorded for each GR at baseline, 1, 5, 10, 15, and 20 years after surgery. Parametric, non‐parametric, and logistic regression statistics were used throughout the study. Results: A total of 21 Class I (44.67%) and 24 Class III (53.33%) GR were treated. Considering all the 45 GR, statistically significant improvements were found for RD in all evaluations ( P  < 0.05) compared with baseline data. Over the course of the study, mean root coverage (MRC) decreased from 74.23% (1 year) to 67.69% (20 years). Within maxillary Class I defects, complete root coverage (CRC) at 1‐year follow‐up was 57.14% (n = 12) and 47.62% (n = 10) at the end of study period, whereas MRC decreased from 82.37% to 77.62%, respectively. Within maxillary Class III recessions, CRC of 20.83% (n = 5) was found at both the 1‐year and the 20‐year follow‐ups. On the other hand, MRC decreased from 66.55% to 58.18%, respectively. The results of logistic regression analysis showed that the achievement of CRC was associated with sites not presenting interdental tissue loss (i.e., Class I, odds ratio: 5.031, P  = 0.024), whereas GR recurrence appeared associated with sites with attached KT < 2 mm (i.e., 5‐, 10‐, 15‐ and 20‐year follow‐ups), to teeth presenting root steps (i.e., 10‐ and 20‐year follow‐ups), and smoking (i.e., 15‐year follow‐up). Conclusions: Positive RD reduction and KT improvements achieved by SCTG + CAF at short‐term may be preserved long‐term with the majority of the treated sites not displaying relapse of the gingival margin. Teeth lacking a minimal 2‐mm width of attached KT and presenting non‐carious cervical lesions were more prone to develop an apical shift of the gingival margin during a 20‐year follow‐up period.